Microbiological quality analysis of commercial fruit juice in Dhaka City, Bangladesh (Stamford Journal of Microbiology, 2019)
The aims of this study were to evaluate the microbiological quality of different commercially available fruit juice of Dhaka city. In this study total 20 fruit juice samples of five different types were repeatedly subjected to bacteriological and mycological screening for three months. Isolates were identified and confirmed using cultural and biochemical characteristics. Current study showed high bacterial and fungal loads consisting of specific pathogens such as coliform and Staphylococcus spp., fecal coliform and other pathogens are totally absent. The presence of Staphylococcus aureus portends health risk to consumers as some species produce potent toxins associated with food borne illnesses. And high bacterial count indicated unhygienic conditions of the processing area, and that good manufacturing practices during processing are not maintained properly. Recommendations are required to reduce the microbiological contamination and promote quality assurance of the products.Stamford Journal of Microbiology, Vol.8(1) 2018: 15-18